Capacitive deionization electrode and capacitive deionization device for selectively removing calcium ions and magnesium ions and application of capacitive deionization electrode and capacitive deionization device

By using the electrode material prepared by titanic acid-alumina composite materials, the selective removal of calcium and magnesium ions in the existing technologies in the existing technology has achieved efficient and stable ion adsorption effects, significantly reduced the water in the water Salt concentration.

CN119349726AActive Publication Date: 2025-01-24CHINA AGRI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411727189.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-01-24
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The existing capacitive deionization technology is difficult to achieve selective removal of calcium and magnesium ions in brackish water, and the adsorption capacity of traditional electrode materials is low.

Method used

The combination of titanate-alumina-alumina composite materials and conductives, adhesives and other combinations to form an efficient selective exfoliating electrode through a burn method or a one-step solid-phase legal spare electrode material.

Benefits of technology

The efficient selective adsorption of calcium and magnesium ions in bitter salt water, significantly improved the adsorption volume and cyclic electrical adsorption stability of the electrode, and reduced the salt concentration in the water.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349726A_ABST
    Figure CN119349726A_ABST
Patent Text Reader

Abstract

According to the capacitive deionization electrode for selectively removing calcium and magnesium ions, the capacitive deionization device and the application of the capacitive deionization electrode, the barium titanate-aluminum oxide composite material is adopted as an active material of the electrode, and the selectivity and performance of the electrode are remarkably improved. The invention also provides a selective capacitive deionization device based on the electrode, the capacitive deionization electrode is used as a core component, the device realizes targeted selective adsorption of calcium and magnesium ions by optimizing the composite structure and surface characteristics of the electrode material, and the device is especially suitable for purification treatment of bitter water in northwest arid regions, and has wide application prospects. The salt concentration in the water is effectively reduced. In addition, the composite material electrode overcomes the limitation of a traditional carbon-based material, the adsorption capacity is remarkably improved, good stability is kept in multiple adsorption-desorption cycles, and the service life of the electrode is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of capacitive deionization, and in particular to a capacitive deionization electrode for selectively removing calcium and magnesium ions, a capacitive deionization device and applications thereof. Background Art

[0002] Brackish water is a water resource with high salt content and bitter taste. It is mainly distributed in the northwest region. The salinity is usually between 1,000-10,000 mg / L. In the agricultural field, the use of brackish water for irrigation will lead to soil salinization, accumulation of salt in the soil, destruction of soil structure, resulting in compaction and particle dispersion, affecting the absorption of water and nutrients, inhibiting crop growth, reducing crop yield and quality, and even leading to land degradation and loss of production capacity in severe cases. In addition, the high concentration of salt in brackish water will increase the osmotic stress of crop roots, leading to water shortage and ion poisoning, affecting the health and output of crops. Calcium and magnesium ions are important nutrients required for plant growth and development, but their excessive amount has a negative impact on plants. Excessive calcium ions may inhibit root elongation, weaken root growth, and affect water and nutrient absorption. Excessive magnesium ions may increase rhizosphere osmotic pressure, making it difficult for plants to absorb water from the soil, leading to drought stress symptoms such as leaf wilting. Therefore, it is necessary to remove excess calcium and magnesium ions in brackish water. Research on removing excess calcium and magnesium ions from water is of great significance for increasing plant yields

[0003] Dialysis, reverse osmosis, membrane treatment and capacitive deionization (CDI) are the main methods for brackish water desalination. Among them, electrodialysis is a technology that uses an electric field to separate and remove ions from a solution; reverse osmosis is a water treatment technology that uses a semipermeable membrane to remove ions, molecules and larger particles from a solution. It has a large initial investment, membrane pollution, and difficult wastewater treatment, and high costs; membrane treatment technology is a water treatment technology that combines ion exchange membranes with capacitive deionization technology, which increases cost and complexity, limits the speed of ion migration, and can also cause membrane pollution, resulting in performance degradation.

[0004] Capacitive deionization technology is a new environmentally friendly brackish water desalination technology. Compared with traditional technologies, it has the advantages of low energy consumption, no secondary pollution and renewable electrodes. At present, the electrodes used for desalination of brackish water using CDI technology are basically made of carbon-based materials, which use the double layer effect to electrically adsorb charged ions in water in a broad spectrum. The core of capacitive deionization is composed of a pair of high-efficiency adsorption electrodes, which often use high specific surface area materials or functionalized composite materials. Through the action of the electric field, positive and negative ions are adsorbed to the positive and negative surfaces of the electrodes respectively, thereby achieving the removal of ions in the water.

[0005] Activated carbon is a common capacitive deionization electrode material, which is widely used due to its high specific surface area, excellent conductivity and low cost. However, it is difficult to selectively remove specific ions in a mixed solution during selective deionization, and its adsorption capacity is low. Therefore, it is urgent to develop new electrode materials for selectively removing ions from water to soften hard water. Summary of the invention

[0006] The inventors have found through research that traditional electrode materials can be modified using composite materials. The composite of traditional electrode materials and conductive polymers can combine the advantages of both and improve the conductivity and selectivity of the electrode. For example, conductive polymers such as polypyrrole and polyaniline can be composited with carbon-based electrode materials to achieve selective adsorption and detection of specific ions by adjusting the structure and functional groups of the polymers.

[0007] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the embodiments of the present invention provide a capacitive deionization electrode for selectively removing calcium and magnesium ions, a capacitive deionization device and its application, which can achieve selective adsorption of calcium and magnesium ions in brackish water.

[0008] In one aspect, an embodiment of the present invention proposes a method for preparing a capacitive deionization electrode for selectively removing calcium and magnesium ions, characterized in that it comprises the following steps: mixing and stirring a barium titanate-aluminum oxide composite material, a conductive agent, an adhesive, and NMP evenly to form a slurry, wherein the mass ratio of the barium titanate-aluminum oxide composite material, the conductive agent, and the adhesive is 80-95:5-10:5-10, and the volume of NMP and the mass ratio of the barium titanate-aluminum oxide composite material are 5-7.5 ml:1 g, the slurry is evenly coated on a current collector, allowed to stand at room temperature, and assembled after drying to obtain a capacitive deionization electrode for selectively removing calcium and magnesium ions.

[0009] In some embodiments, the preparation method of the barium titanate-aluminum oxide composite material is a calcination method or a one-step solid phase method, wherein the calcination method comprises the following steps:

[0010] Dissolve titanate in deionized water, add alcohol, stir until completely dissolved, add an appropriate amount of aluminum salt solution and continue stirring, wherein the concentration of titanate and aluminum salt solution are both 1 mol / L, and the volume ratio of titanate to aluminum salt solution is 1:2, stir until the solution becomes transparent and there are no obvious bubbles, remove the solvent, wash the precipitate, and then dry it at 80-120°C, then put the precipitate into a muffle furnace and calcine it at 700-800°C for 2-4 hours, cool it to room temperature and take it out to obtain a barium titanate-alumina composite material;

[0011] The one-step solid phase method includes the following steps:

[0012] The barium titanate powder and the alumina powder are mixed in a mass ratio of 1:2, and deionized water is added, wherein the volume of the deionized water is 20-30% of the total mass of the barium titanate powder and the alumina powder. The mixture is stirred evenly for 30-40 minutes, and then calcined at a temperature of 900-1000°C for 2-3 hours to obtain a barium titanate-alumina composite material.

[0013] In some embodiments, the barium titanate-aluminum oxide composite material is in the form of nanoparticles, nanosheets or nanorods. When the barium titanate-aluminum oxide composite material is in the form of nanoparticles, the particle size of the nanoparticles is 100-400 nm.

[0014] In some embodiments, the barium titanate-aluminum oxide composite nanoparticles have a particle size of 250 nm.

[0015] In some embodiments, the conductive agent is acetylene black or carbon black, the adhesive is PVDF, PTFE or Nafion, and the current collector is titanium sheet, graphite paper or carbon paper.

[0016] The second embodiment of the present invention provides a capacitor deionization electrode prepared by the above-mentioned preparation method.

[0017] A third aspect of the present invention provides a capacitive deionization device, comprising a positive electrode and a negative electrode, wherein the negative electrode is the capacitive deionization electrode described above, and the positive electrode is an electrode using carbon material as an active material.

[0018] A fourth aspect of the present invention provides an application of a capacitive deionization device in the desalination of brackish water, and utilizes the capacitive deionization device to selectively adsorb calcium and magnesium ions in the brackish water.

[0019] In some embodiments, the positive and negative voltages of the capacitive deionization device are 0.8-1.8V. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings.

[0021] in:

[0022] Figure 1 is a schematic structural diagram of a capacitive deionization device in an embodiment of the present invention;

[0023] Figure 2 The barium titanate-aluminum oxide composite material and the activated carbon material adsorb Ca in the mixed solution at 1.8 V in Example 3 of the present invention. 2+ Mg 2+ 、Na + , Cl - Comparison chart of unit desalination capacity;

[0024] Figure 3 The barium titanate-aluminum oxide composite material and the activated carbon material adsorb Ca in the mixed solution at 1.8 V in Example 3 of the present invention. 2+ Mg 2+ 、Na + , Cl - Comparison chart of 60 ion cycle removal rates;

[0025] Figure 4 This is a test diagram of calcium ion adsorption performance of the barium titanate aluminum oxide composite material under different voltages in Example 3 of the present invention;

[0026] Figure 5 This is a test diagram of the magnesium ion adsorption performance of the barium titanate aluminum oxide composite material under different voltages in Example 3 of the present invention;

[0027] Figure 6 It is a test diagram of the calcium ion adsorption performance of the activated carbon material in the comparative example under different voltages;

[0028] Figure 7 It is a test diagram of the adsorption performance of magnesium ions of the activated carbon material in the comparative example at different voltages;

[0029] Description of reference numerals:

[0030] 1. Glass plate; 2. Silicone sheet; 3. Current collector; 4. Plastic gasket. DETAILED DESCRIPTION

[0031] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.

[0032] The following describes a capacitive deionization electrode for selectively removing calcium and magnesium ions, a capacitive deionization device, and applications thereof according to embodiments of the present invention with reference to the accompanying drawings.

[0033] In one aspect, an embodiment of the present invention proposes a method for preparing a capacitive deionization electrode for selectively removing calcium and magnesium ions, characterized in that it comprises the following steps: mixing and stirring a barium titanate-aluminum oxide composite material, a conductive agent, an adhesive, and NMP evenly to form a slurry, wherein the mass ratio of the barium titanate-aluminum oxide composite material, the conductive agent, and the adhesive is 80-95:5-10:5-10, and the volume of NMP and the mass ratio of the barium titanate-aluminum oxide composite material are 5-7.5 ml:1 g, and the slurry is evenly coated on the current collector 3, allowed to stand at room temperature, and assembled after drying to obtain a capacitive deionization electrode for selectively removing calcium and magnesium ions.

[0034] The embodiment of the present invention can be prepared into a capacitor deionization electrode material through the above method, which can selectively adsorb calcium and magnesium ions in water with a large adsorption capacity. Compared with the traditional electrode material nitrogen-doped carbon, the capacitor deionization electrode material prepared by the embodiment of the present invention is green, efficient, low-carbon, and sustainable, and plays an important role in responding to major challenges such as resource shortages, energy crises, and environmental degradation.

[0035] The embodiment of the present invention uses a barium titanate-aluminum oxide composite material as the active material of the electrode, which significantly improves the selectivity and performance of the electrode.

[0036] It should be noted that the coating thickness of the slurry on the current collector 3 can be adjusted according to actual needs.

[0037] In some embodiments, the preparation method of the barium titanate-aluminum oxide composite material is a calcination method or a one-step solid phase method, wherein the calcination method comprises the following steps:

[0038] Dissolve titanate in deionized water, add alcohol, stir until completely dissolved, add an appropriate amount of aluminum salt solution and continue stirring, wherein the concentration of titanate and aluminum salt solution are both 1 mol / L, and the volume ratio of titanate to aluminum salt solution is 1:2, stir until the solution becomes transparent and there are no obvious bubbles, remove the solvent, wash the precipitate, and then dry it at 80-120°C, then put the precipitate into a muffle furnace and calcine it at 700-800°C for 2-4 hours, cool it to room temperature and take it out to obtain a barium titanate-alumina composite material;

[0039] The one-step solid phase method includes the following steps:

[0040] The barium titanate powder and the alumina powder are mixed in a mass ratio of 1:2, and deionized water is added, wherein the volume of the deionized water is 20-30% of the total mass of the barium titanate powder and the alumina powder. The mixture is stirred evenly for 30-40 minutes, and then calcined at a temperature of 900-1000°C for 2-3 hours to obtain a barium titanate-alumina composite material.

[0041] It should be noted that both preparation methods are acceptable and can be selected according to actual conditions.

[0042] In some embodiments, the barium titanate-aluminum oxide composite material is in the form of nanoparticles, nanosheets or nanorods. When the barium titanate-aluminum oxide composite material is in the form of nanoparticles, the particle size of the nanoparticles is 100-400 nm.

[0043] In some embodiments, the particle size of the barium titanate-aluminum oxide composite nanoparticles is 250 nm, which can make the prepared capacitor deionization electrode have better selective adsorption and greater adsorption capacity for calcium and magnesium ions.

[0044] In some embodiments, the conductive agent is acetylene black or carbon black, the adhesive is PVDF, PTFE or Nafion, and the current collector 3 is a titanium sheet, graphite paper or carbon paper.

[0045] It should be noted that the full name of Nafion is perfluorosulfonic acid polymer, and its Chinese name is naphthol. It is a polymer with ionic properties and can be used as an adhesive.

[0046] The second embodiment of the present invention provides a capacitor deionization electrode prepared by the above-mentioned preparation method. Due to the addition of barium titanate-aluminum oxide, the electrode of the embodiment of the present invention overcomes the limitations of traditional carbon-based materials, not only improves the adsorption capacity of calcium and magnesium ions by the electrode, but also makes the electrode have excellent cyclic electrosorption stability, can achieve more than 2 cyclic electrosorption, and prolongs the service life of the electrode.

[0047] A third aspect of the present invention provides a capacitive deionization device, comprising a positive electrode and a negative electrode, wherein the negative electrode is the capacitive deionization electrode described above, and the positive electrode is an electrode using carbon material as an active material.

[0048] The capacitor deionization device of the embodiment of the present invention achieves targeted selective adsorption of calcium and magnesium ions by optimizing the composite structure and surface characteristics of the electrode material, and has a wide range of application potentials. It can optimize the treatment of water sources with different salt compositions, especially in the field of brackish water desalination and resource recovery. It provides an efficient and economical water resource purification solution for the arid and semi-arid areas of Northwest China. The capacitor deionization device utilizes the synergistic effect of the high dielectric properties of barium titanate and the excellent chemical stability of aluminum oxide, so that the electrode exhibits excellent selective adsorption capacity and significant desalination efficiency in the process of removing calcium and magnesium ions from brackish water, effectively reducing the salt concentration in the water.

[0049] like Figure 1 As shown, the capacitive deionization device includes a glass plate 1, a silicone sheet 2, a current collector 3, and a plastic gasket 4, wherein the positive electrode and the negative electrode are respectively located on the current collectors 3 on both sides.

[0050] In practical applications, regeneration can be achieved by short-circuiting the positive and negative electrodes after electrical adsorption.

[0051] A fourth aspect of the present invention provides an application of a capacitive deionization device in the desalination of brackish water, and utilizes the capacitive deionization device to selectively adsorb calcium and magnesium ions in the brackish water.

[0052] It should be noted that brackish water refers to water containing a relatively high concentration of soluble salts (such as chlorides, sulfates) and hardness ions (calcium ions and magnesium ions). The salt substances in brackish water not only affect the hardness of the water, but also give the water a significant bitter and salty taste. Its total dissolved solids (TDS) content is usually higher than 1000ppm, which is significantly higher than ordinary drinking water. The cations in brackish water include calcium ions, magnesium ions, sodium ions, and potassium ions, and the anions include chloride ions, nitrate ions, and sulfate ions. Among them, calcium ions and magnesium ions are the main ions that need to be removed.

[0053] The capacitive deionization device of the embodiment of the present invention has a high adsorption capacity for calcium and magnesium ions in brackish water, effectively solving the problem of capacity limitation when using carbon materials as electrodes, has strong universality, simple operation, and does not require the addition of ion exchange membranes.

[0054] In some embodiments, the positive and negative voltages of the capacitive deionization device are 0.8-1.8 V, so that the adsorption of calcium and magnesium ions reaches the maximum value and the adsorption is stable. If it is lower than 0.8 V or higher than 1.8 V, the adsorption of calcium and magnesium ions will decrease.

[0055] The present invention is further described below through specific examples.

[0056] Example 1

[0057] A preparation method of a barium titanate-aluminum oxide composite material comprises the following steps: taking 500 mL of deionized water, adding 200 mg of tetraisopropyl titanate, stirring thoroughly to dissolve it, then slowly adding 100 mL of anhydrous ethanol, and continuing to stir evenly. Then, the above solution is slowly added dropwise to 200 mL of 5% aluminum nitrate solution under stirring, and stirring is continued for 2 hours to ensure sufficient reaction. After the reaction is completed, the mixture is centrifuged, the precipitate is washed with deionized water 3 times, and then placed in an 80°C oven for drying for 10 hours. The dried sample is placed in a muffle furnace, heated to 700°C at a heating rate of 5°C / min, and kept calcined for 4 hours, and taken out after cooling to room temperature to obtain a barium titanate-aluminum oxide composite material.

[0058] A capacitive deionization device, using the above electrode as a negative electrode and an electrode using a carbon material as an active material as a positive electrode, according to Figure 1 The method shown constitutes a capacitive deionization device, which is used to selectively adsorb the mixed solution.

[0059] Example 2

[0060] A preparation method of a barium titanate-aluminum oxide composite material comprises the following steps: taking 500 mL of deionized water, adding 250 mg of tetrabutyl titanate, stirring thoroughly at room temperature until completely dissolved, then slowly adding 150 mL of anhydrous ethanol, and continuing to stir evenly. The above solution is slowly added dropwise to 300 mL of a 10% aluminum chloride solution under stirring, and stirring is maintained for 3 hours during the reaction to ensure sufficient reaction. After the reaction is completed, the mixture is allowed to stand and precipitate, and the precipitate is washed 3 times with deionized water and anhydrous ethanol respectively, and then placed in an 80°C oven for drying for 10 hours. The dried sample is placed in a muffle furnace, heated to 800°C at a heating rate of 10°C / min, and kept calcined for 3 hours, and taken out after cooling to room temperature to obtain a barium titanate-aluminum oxide composite material.

[0061] A capacitive deionization device, using the above electrode as a negative electrode and an electrode using a carbon material as an active material as a positive electrode, according to Figure 1 The method shown constitutes a capacitive deionization device, which is used to selectively adsorb the mixed solution.

[0062] Example 3

[0063] A preparation method of a barium titanate-aluminum oxide composite material comprises the following steps: taking 500 mL of deionized water, adding 300 mg of tetraethyl titanate, stirring thoroughly at 60°C until completely dissolved, then slowly adding 200 mL of anhydrous isopropanol, and continuing to stir evenly. The above solution is slowly added dropwise to 400 mL of a 7% aluminum sulfate solution under stirring, and stirring is maintained for 4 hours during the reaction to ensure sufficient reaction. After the reaction is completed, the mixture is centrifuged, the precipitate is washed 3 times with deionized water and isopropanol respectively, and then placed in an 80°C oven for drying for 10 hours. The dried sample is placed in a muffle furnace, heated to 750°C at a heating rate of 8°C / min, and kept calcined for 2 hours, and taken out after cooling to room temperature to obtain a barium titanate-aluminum oxide composite material.

[0064] A capacitive deionization device, using the above electrode as a negative electrode and an electrode using a carbon material as an active material as a positive electrode, according to Figure 1 The method shown constitutes a capacitive deionization device, which is used to selectively adsorb the mixed solution.

[0065] test:

[0066] Take 2 g of the barium titanate-alumina composite material sample prepared in Example 3, put the barium titanate-alumina composite material, conductive carbon black, and PVDF into a test tube at a mass ratio of 8:1:1, add 11 ml of NMP, put it into a centrifugal device, shake it for 4 hours, and then evenly apply it on a 12 cm × 12 cm titanium sheet, let it stand at room temperature for 2 hours, and transfer it to an oven at 80°C for drying for 8 hours.

[0067] The prepared titanium sheet was loaded into a small CDI module (electrode size 12*12cm), and the applied voltages were 1.2V, 1.4V, 1.6V, and 1.8V, respectively. The flow rate was 12ml / min, and the treated water sample was simulated brackish water from Xinjiang Alaer, where Na + The content is about 1200mg / L, Ca 2+ The content is about 500mg / L, Mg 2+ The content is about 100mg / L, K + The content is about 20mg / L, Cl - The content is about 1000mg / L, SO4 2- The content is about 200 mg / L, the salt ratio is NaCl: MgCl2: Na2SO4: CaCl2: KCl = 46: 5: 7: 25: 1, and 250 ml of the prepared brackish water is taken to test the electrode CDI adsorption and desorption cycle performance. At the same time, a capacitive deionization device using activated carbon material as an electrode is used as a comparative example, and the conditions are the same as above.

[0068] The results are as follows: Figure 2 , Figure 3 As shown, the adsorption of Ca by barium titanate alumina composite material and activated carbon material in mixed solution under 1.8V condition 2+ and Mg 2+ The unit desalination capacity and 60 ion cycle removal rate. It can be seen that the barium titanate alumina composite material adsorbs Ca 2+ and Mg 2+ The effect is significantly stronger than that of activated carbon. Figure 4-7 The figure shows the comparison of the adsorption performance of calcium and magnesium ions of barium titanate alumina composite material and activated carbon material at a flow rate of 12 mL / min and at different voltages. Figure 4 This is a test diagram of the calcium ion adsorption performance of barium titanate alumina composite materials under different voltages. Figure 5 This is a test diagram of the adsorption performance of magnesium ions on barium titanate alumina composite materials at different voltages. Figure 6 This is a test chart of the calcium ion adsorption performance of activated carbon materials under different voltages. Figure 7 This is a test chart of the adsorption performance of magnesium ions of activated carbon materials under different voltages.

[0069] It can be seen that the ability of barium titanate alumina composite materials to remove calcium and magnesium ions is significantly higher than that of activated carbon materials. It can also be seen that under the same conditions, the positive and negative voltage values ​​of the capacitor deionization device are 1.8V, compared with 1.2V, 1.4V, and 1.6V, and the ion removal effect is the best, that is, the adsorption of calcium and magnesium ions is the largest.

[0070] The test materials and reagents used in the above examples, unless otherwise specified, can be obtained from commercial sources. If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the field or according to the product instructions.

[0071] In the present invention, the term "some embodiments" and the like means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments in a suitable manner. In addition, those skilled in the art can combine and combine the different embodiments and features of the different embodiments described in this specification without contradiction.

[0072] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing a capacitive deionization electrode for selectively removing calcium and magnesium ions, characterized in that: The steps include: The barium titanate-aluminum oxide composite material, a conductive agent, an adhesive and NMP are mixed and stirred evenly to form a slurry, wherein the mass ratio of the barium titanate-aluminum oxide composite material, the conductive agent and the adhesive is 80-95:5-10:5-10, and the mass ratio of the volume of NMP to the barium titanate-aluminum oxide composite material is 5-7.5 ml:1 g. The slurry is evenly coated on the current collector, allowed to stand at room temperature, and assembled after drying to obtain a capacitive deionization electrode for selectively removing calcium and magnesium ions.

2. The preparation method according to claim 1, characterized in that: The preparation method of the barium titanate-aluminum oxide composite material is a calcination method or a one-step solid phase method, wherein the calcination method comprises the following steps: Dissolve titanate in deionized water, add alcohol, stir until completely dissolved, add an appropriate amount of aluminum salt solution and continue stirring, wherein the concentration of titanate and aluminum salt solution are both 1 mol / L, and the volume ratio of titanate to aluminum salt solution is 1:2, stir until the solution becomes transparent and there are no obvious bubbles, remove the solvent, wash the precipitate, and then dry it at 80-120°C, then put the precipitate into a muffle furnace and calcine it at 700-800°C for 2-4 hours, cool it to room temperature and take it out to obtain a barium titanate-alumina composite material; The one-step solid phase method includes the following steps: The barium titanate powder and the alumina powder are mixed in a mass ratio of 1:2, and deionized water is added, wherein the volume of the deionized water is 20-30% of the total mass of the barium titanate powder and the alumina powder. The mixture is stirred evenly for 30-40 minutes, and then calcined at a temperature of 900-1000°C for 2-3 hours to obtain a barium titanate-alumina composite material.

3. The preparation method according to claim 1, characterized in that: The barium titanate-aluminum oxide composite material is in the form of nanoparticles, nanosheets or nanorods. When the barium titanate-aluminum oxide composite material is in the form of nanoparticles, the particle size of the nanoparticles is 100-400 nm.

4. The preparation method according to claim 1, characterized in that: The particle size of the barium titanate-aluminum oxide composite nanoparticles is 250 nm.

5. The preparation method according to claim 1, characterized in that: The conductive agent is acetylene black or carbon black, the adhesive is PVDF, PTFE or Nafion, and the current collector is titanium sheet, graphite paper or carbon paper.

6. A capacitor deionization electrode prepared by the preparation method according to any one of claims 1 to 5.

7. A capacitive deionization device, comprising a positive electrode and a negative electrode, characterized in that: The negative electrode is the capacitor deionization electrode as claimed in claim 6, and the positive electrode is an electrode using carbon material as an active material.

8. Application of a capacitive deionization device in brackish water desalination, characterized in that: The capacitive deionization device according to claim 7 is used to selectively adsorb calcium and magnesium ions in brackish water.

9. The use according to claim 8, characterized in that: The positive and negative pole voltages of the capacitive deionization device are 0.8-1.8V.

Citation Information

Patent Citations

  • Active material, adsorption electrode, capacitive deionization device, preparation method and application thereof

    CN114084940A

  • Capacitive deionization electrodes and production methods thereof, and capacitive deionization apparatus including the same

    KR1020150035265A